Client Satisfaction with Delivery Care Service and Associated Factors in the Public Health Facilities of Gamo Gofa Zone, Southwest Ethiopia: In a Resource Limited Setting. (20th June 2016) - Tesfaye, Rahel; Worku, Amare; Godana, Wanzahun; Lindtjorn, Bernt
Abstract : Background . Ensuring patient satisfaction is an important means of secondary prevention of maternal mortality. This study presents findings from a multidimensional study of client satisfaction from the Gamo Gofa Zone in Southwest Ethiopia. Methods . A facility based cross-sectional study using exit interviews was conducted from 2014. Client satisfaction was measured using a survey adopted from the Donabedian quality assessment framework. Thirteen health institutions were randomly sampled of 66 institutions in Gamo Gofa Zone. Logistic regression was used to determine predictors of client satisfaction. Results . The overall satisfaction level of the clients in this study was 79.1% with (95% CI; 75–82). Women attending health centres were more likely satisfied than women attending hospitals (χ 2 = 83.7, d f = 12, P < 0.001 ). The proportion of women who complained about an unfriendly attitude or unresentful care from health workers was higher in the hospitals (χ 2 = 27.4, d f = 1, P < 0.001 ). The presence of support persons during child birth improved client satisfaction (AOR = 6.23 95% CI; 2.75–14.1) and women who delivered with caesarean section are four times more likely satisfied than those who deliver vaginally (AOR 3.6 95% CI; 1.44–9.06). Client satisfaction was reduced if the women had to pay for the services (AOR = 0.27 95% CI; 0.09–81). Conclusions . The study shows that overall satisfaction level is good. More emphasis should be put on giving women friendly care, particularly at the hospitals.